Hello.
-7h + 2(-4h + 5) > -4h + 1 + 10 ; solve for h
Our first step is to get rid of all the parenthesis. We can do this by simplifying everything out.
-7h - 8h + 10 > -4h + 11
Add like terms.
-15h + 10 > -4h + 11
Now, we must isolate our variables. We do this by moving all variables to one side and moving our other numbers to the other.
Subtract 10 from both sides. Then, add 4h to both sides.
-15h + 4h > 11 - 10
Simplify.
-h > 1
Divide both sides by -1.
However, keep in mind that when dividing with a negative, you must change the sign. Therefore, > turns into <
-h ÷ -1 < 1 ÷ -1
h < -1
Combine like-terms
-2.1x and 4.9x = 2.8x
3.7 and 5 = 8.7
2.8x + 8.7 is your final answer.
Answer:
the distance of the Bird (B) from the plane (P) is = 10779 ft
Step-by-step explanation:
From the given information:
a diagrammatic representation is attached below for better understanding and solution to the question.
From the diagram;
Let the Bird (B) be represent as A
The plane (P) be represented by B
The observer be represented by O
and the tower T be represented by C
we will see that:
![\overline {AB} \ \| \ \overline {OC}](https://tex.z-dn.net/?f=%5Coverline%20%7BAB%7D%20%20%5C%20%5C%7C%20%5C%20%5Coverline%20%7BOC%7D)
Also;
![\angle ABO = \angle BOC = 33^0](https://tex.z-dn.net/?f=%5Cangle%20ABO%20%3D%20%5Cangle%20BOC%20%3D%2033%5E0)
AO = BC = 7000
Let consider the trigonometry of triangle BAO
tan θ = opposite/adjacent
tan 33° = 7000/x
0.6494 = 7000/x
x = 7000/0.6494
x = 10779.18
x = 10779 ft ( to the nearest whole number)
Thus; the distance of the Bird (B) from the plane (P) is = 10779 ft
Answer:
1.(6*4) + (18*6) + (6*4)
1.(6*10) + (6*6) + (6*10)
Step-by-step explanation:
there are two ways to break this shape into three rectangles:
1.Top right rectangle, Top left rectangle, Bottom long rectangle
2. Left rectangle, Middle square, Right rectangle.
Answer:
a - 2
Step-by-step explanation:
Perimeter = side 1 + side 2 + side 3
So
6a + 3 = 2(a + 3) + (3a - 1) + side 3
side 3 = (6a + 3) - (2a + 6) - (3a - 1)
side 3 = 6a - 2a - 3a + 3 - 6 + 1 = a - 2